PENGARUH RETURN ON EQUITY DAN NILAI DEVIDEN TERHADAP KEPUTUSAN INVESTASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Wayan Suryathi (STIE BIITM, 2020)
Abstract The purpose of this study is to determine and analyze the effect of partially and simultaneously return on equity and dividend value on investment decisions on Companies Listed on the Indonesia Stock Exchange. The research method used consisted of data types namely quantitative data. The data source is a secondary data source. Data collection techniques through documentation study. The analysis technique uses quantitative analysis with the help of SPSS statistics. Based on the results of the analysis and discussion it can be concluded that there is no significant effect between the ROE variable (X1) on investment decisions (Y). This can be seen from the t-count value of ROE (X1) of 1.062, with a significant value of 0.295> 0.05. Dividend value (X2) also does not have a significant effect on investment decisions (Y). This can be seen from the t-value of the dividend value of -1.273, with a significant value of 0.211> 0.05. Likewise, there is no significant effect simultaneously between the independent variable ROE and dividend value on the dependent variable of investment decisions on Companies Listed on the Indonesia Stock Exchange with a coefficient value of F is 1,150 with a coefficient of sig 0,328, which means> 0.05.